Mechanical and Thermal Properties of Cellulose Nanofiber-Reinforced Polypropylene Composites Compatibilized with PP-g-MA - Azhary, Taufik; Azhar, Faruq Avero (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2026)
Polypropylene is widely used in the automotive industry because it is lightweight, inexpensive, and easy to process, but it has limitations, including relatively low mechanical properties and a tendency to shrink. Cellulose nanofiber is used as an environmentally friendly reinforcement with high strength, but differences in properties between hydrophobic polypropylene and hydrophilic CNF result in poor compatibility. To overcome this, a polypropylene-graft-maleic anhydride (PP-g-MA) coupling agent is added to enhance interfacial bonding. This study aims to evaluate the effects of CNF and PP-g-MA content on the mechanical properties, thermal stability, and water resistance of polypropylene materials produced by extrusion and injection molding. The outcomes show that substituting 1 wt% CNF provides significant reinforcement, elevating the tensile strength to 22.90 MPa and the flexural strength to 29.70 MPa. At higher CNF contents, agglomeration occurs, leading to decreased mechanical properties and increased water absorption up to 0.35%. The substitution of PP-g-MA increased the compatibility of the PP/CNF composite, as indicated by the appearance of an ester peak in the FTIR, an increase in crystallinity in the DSC/XRD, and a shift in the onset of degradation by 340°C to 350°C in the PP/1CNF/5PP-g-MA composite. This formulation also produced a tensile strength of 25.60 MPa, a flexural strength of 33.00 MPa, and low water absorption. Although substituting CNF reduced impact strength, using PP-g-MA restored impact strength to near that of pure polypropylene. Overall, the PP/1CNF/5PP-g-MA composite was determined to be the optimal composition due to its balanced mechanical properties, thermal stability, and water resistance.